In silico structural analysis, physicochemical characterization and homology modeling of transmembrane protein 43 (TMEM 43) - Rabbi, Mir Sohayeb (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017